Accessibility and Affordability Impacts of Half Price Public Transport Fares in Aotearoa New Zealand - Angela Curl; Anna Coppens; Cushla Dares; Jonathan Williman; Helen Fitt; Simon Kingham (Findings)
Transport costs can constitute a large proportion of household budgets and restrict travel.